2018
DOI: 10.1016/j.landusepol.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Towards incorporating location choice into integrated land use and transport planning and policy: A multi-scale analysis of residential and job location choice behaviour

Abstract: Towards incorporating location choice into integrated land use and transport planning and policy: A multi-scale analysis of residential and job location choice behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
2
12
0
3
Order By: Relevance
“…The key findings of this study suggest integrating the transportation planning with the housing development sector as it is found that many of the residential location choices are based on transportation factors, mainly the availability of public transport, car ownership, and transport modes. It is in confirmation with the findings of recent relevant studies conducted both in developed (Bruns and Matthes 2019;Ho et al 2017) and developing countries (Acheampong 2018). This provides a rationale that the Egyptian government needs to invest in the public transport sector to make it integrated and efficient simultaneously to the development of new cities to address the housing needs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The key findings of this study suggest integrating the transportation planning with the housing development sector as it is found that many of the residential location choices are based on transportation factors, mainly the availability of public transport, car ownership, and transport modes. It is in confirmation with the findings of recent relevant studies conducted both in developed (Bruns and Matthes 2019;Ho et al 2017) and developing countries (Acheampong 2018). This provides a rationale that the Egyptian government needs to invest in the public transport sector to make it integrated and efficient simultaneously to the development of new cities to address the housing needs.…”
Section: Discussionsupporting
confidence: 85%
“…However, the effects of such transport planning measures on the residential location choices have not been entirely clear (Cao et al 2009). Nevertheless, integrating transport planning decisions with residential location choices has been suggested for sustainable urban development (Acheampong 2018). The process of residential location choices does not contest integrated land use and transportation (ILUT) strategies rather it finds complementarities with ILUT strategies (Bruns and Matthes 2019), and thus, residential location choices need to be integrated with transport and land use models (Ho et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A group or cluster is created in which objects belonging to a group are more similar to one another than in other groups (Rokach & Maimon, 2005). Research has identified the impact of housing and job choices on the urban structure in surveys using a representative sample (Acheampong, 2018). A cluster sampling (Zhao et al, 2019) is used to classify large-scale data and the ability of each sample category to access the sample.…”
Section: Methodology For Evaluation Of Residential Plot Selection In mentioning
confidence: 99%
“…Acquisition of housing starts from the location and plot selection. If one of the biggest influences on the choice of place of residence was the infrastructure 10−20 years ago, this aspect becomes less significant in the present time as the number of cars in families increases (Baušys & Juodagalvienė, 2017;Acheampong, 2018). Environmental pollution becomes more relevant (Kerimray et al, 2018), proximity to nature, projected global development of adjacent areas (Fatmi & Habib, 2018;Tao, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation